2015
DOI: 10.5005/jp-journals-10009-1402
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Congenital Anomalies during Routine Fetal Surveillance

Abstract: Background Birth defects are common in human development. Approximately 3% of newborns have a recognizable major anomaly, and at least 5% will ultimately be diagnosed with a congenital defect. Because of improvements in other areas of prenatal care, birth defects are the single most common cause of perinatal mortality in developed countries, accounting 20 to 25% of perinatal deaths. Now, many genetic and other disorders can be diagnosed early in pregnancy. Screening examinations during pregnancy are an essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…It can be concluded that ultrasound application for fetal surveillance is one of the most important tools for evaluation of fetal well-being and diagnosis of different, major and minor, anomalies which if detected on time can rescue the mother and fetal life by changing the way of managing the pregnancy and delivery. 6 This is seen in the last case where a minor anomaly was detected but on meticulous follow-up repeat scan the anomaly disappeared. Complications were observed in the first and fourth cases.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…It can be concluded that ultrasound application for fetal surveillance is one of the most important tools for evaluation of fetal well-being and diagnosis of different, major and minor, anomalies which if detected on time can rescue the mother and fetal life by changing the way of managing the pregnancy and delivery. 6 This is seen in the last case where a minor anomaly was detected but on meticulous follow-up repeat scan the anomaly disappeared. Complications were observed in the first and fourth cases.…”
Section: Discussionmentioning
confidence: 88%
“…5 About 20% of anomalies in live-born infants are based on defective gene, 10% are due to chromosomal abnormalities, and 10% are due to exogenous injury to the conceptus. 6 Some 60% of all congenital anomalies are of indeterminate cause or are multifactorial in origin (due to hereditary or environmental factors). 6 In Africa, all these factors may play a role, for example, nutritional deficiencies (folic acid, iodine), maternal diseases (diabetes, thyroid diseases), maternal exposure to harmful substances in pregnancy (lead, dichlorodiphenyltrichloroethane, radiations), maternal infections in pregnancy (rubella, cytomegalovirus, Zika virus, syphilis), use of herbal concoctions as medication which may potentially contain teratogenic agents in pregnancy, and pregnancy at or above 35 years.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations